Implementation of Waste Battery Energy Collection System - Li Chao; Yi Bo-nian (Institute of Advanced Engineering and Science, 2013)
In this energy collection system, it uses Boost and Buck circuits. If the input voltage is too low, low power supply chip will be active ,making the charging voltage at an appropriate range. In order to measure the input voltage, output voltage and the current, high-precision chips are used, cooperated with 32-bits-high-speed CPU to make sure the output voltage stable. This system has a perfect over-current ,over-voltage protection function. The system uses the high efficient switch power supply. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2683